Development of Zinc Oxide Nanoparticle–Infused Carrageenan Membranes with Enhanced Structural and Antimicrobial Properties for Guided Tissue Regeneration - P T, PRIYANGHA; M, Ashritha; S, Balaji Ganesh (Biomedical Sciences and Clinical Medicine, 2025)
Objective The fundamental aim of periodontal therapy is to promote the regeneration of tissues affected by the disease. In recent times, there has been a rising trend in using guided tissue regeneration (GTR) membranes. These membranes are increasingly relied upon to direct the growth of gingival tissue away from the root surface. Both resorbable and non-resorbable membranes presently in use serve as physical barriers, hindering the infiltration of connective and epithelial tissues into the defect area, thus fostering periodontal tissue regeneration. This study aims to develop a polymeric membrane reinforced with carrageenan and zinc oxide nanoparticles and assess its potential for periodontal regeneration. Methods 3g of dried Kappaphycus was mixed with 100 mL of distilled water in a container and autoclaved for 15 minutes at 121 degrees Celsius. After cooling, the mixture was blended thoroughly for carrageenan extraction. Then, 1.5 g of PEG 6000 was added as a plasticizer. Zinc oxide nanoparticles (ZnO) were added and homogenized into the carrageenan extract. The mixture was microwave-boiled for 2 minutes, poured onto a petri dish, and air-dried for 24 hours. Further drying at 50 degrees Celsius for 2 hours ensured complete moisture removal. Finally, the membrane was carefully peeled from the petri dish for testing and use. The membrane underwent SEM, tensile strength, Fourier transform infrared, and antimicrobial activity analysis. Results Scanning electron microscopy analysis revealed a densely packed and moderately rough surface in the ZnO-incorporated membrane, with a broader particle size distribution (1.28 ± 3.67 µm) compared to the smoother carrageenan-only membrane (1.15 ± 1.68 µm). Tensile testing showed improved mechanical strength in the ZnO composite (6.89 MPa) relative to the plain carrageenan membrane (5.39 MPa). FTIR spectra confirmed successful integration of ZnO nanoparticles through characteristic Zn–O peaks, along with preserved polysaccharide functional groups. Antimicrobial activity, evaluated via OD600 measurements over 4 hours, demonstrated time- and size-dependent bacterial inhibition against S. mutans, with the 4 cm² membrane showing superior performance, comparable or superior to chloramphenicol at later time points. Conclusions The developed membrane reinforced with carrageenan and zinc oxide nanoparticles exhibited adequate tensile strength and sufficient antimicrobial properties, suggesting its suitability for utilization in periodontal therapy as an effective regenerative material.